The induction of acid tolerance in Vibrio cholerae - factors influencing and cross-protection responses / Anneeza Zaity Zainal - Zainal, Anneeza Zaity (2007)
The factors influencing the ability of Vibrio cholerae AC-V99 El Tor 01 Ogawa to tolerate acid killing after a pre-exposure to sub-lethal acid pH were studied. The effect of pre-exposure to sub-lethal acid pH on tolerance to other stresse s (cross-protection) including heat, osmotic and oxidative stresses was also investigated. The involvement of de novo proteins synthesis and effect on cell morphology were also determined . Acid sensitivity test showed that the sublethal pHs for this strain ranged from pH 5.0 to pH 6.0 and at pH 4.5 and below the cells are completely killed. The ability of this bacterium to induce acid tolerance was tested by pre-exposing early exponential cells in LB + 3% NaCl at pH 5.0 for one hour before challenging them to pHs 3.5, 3.0 and 2.5 for a further one hour. Viable counts were determined by plating dilutions of the samples on LB + 3% agar (pH 7.0) at various intervals of time. Cells that were pre-exposed to pH 5.0 survived significantly better (P < 0.05) at these lethal pHs compared to those that were pre-exposed to pH 7.0. This response is partly dependent on de novo protein synthesis as treatment with chloramphenicol, a protein synthesis inhibitor during pre-exposure did not completely eliminate the respon se. Microscopic examination showed that acid induced cells were found to be elongated and segmented probably due to arrested cell division. The induct ion of acid tolerance response was found to be affected by growth phase, pH, temperature, pre-exposure time and initial cell density. Early exponential phase cells pre-exposed to pH 5.0 were found to have highest survival rate after one hour of challenge at pH 3.5 followed by stationary phase, late exponential phase and mid-exponential phase cells under the same conditions. A preexposure at pH 5.0 for three hours gave maximal protection against acid killing compared to one, two and three hours of pre-exposure time…